2023
DOI: 10.3389/fenrg.2023.1061221
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal effects of China’s digital economy on rural revitalization

Abstract: The paper constructs an evaluation index system of China’s digital economy and rural revitalization development, including 46 indicators of digital economy and rural revitalization subsystem, and analyzes the impact of China’s digital economy on rural revitalization by combining spatial Markov analysis method and spatial econometric model, and finds that:① The spatial heterogeneity of rural revitalization pattern is obvious, and the difference between north and south is more prominent, and the spatial clusteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Comparing the two figures, it can be found that: firstly, from 2011 to 2021, the level of IE in each province has been increasing, and the inter-provincial gap has been decreasing. This suggests that China's policy initiatives for IE have achieved some success, and the digital economy can effectively reduce regional disparities (Zhou et al, 2023), which is consistent with the findings of (Zhang et al, 2022). The spatial distribution of IE shows the trend of "decreasing from the east to the west", and regional disparities are reduced over time, which is similar to the results of the study of (Wu et al, 2023).…”
Section: The Time Evolution and Spatial Distribution Of Ie And Cesupporting
confidence: 86%
“…Comparing the two figures, it can be found that: firstly, from 2011 to 2021, the level of IE in each province has been increasing, and the inter-provincial gap has been decreasing. This suggests that China's policy initiatives for IE have achieved some success, and the digital economy can effectively reduce regional disparities (Zhou et al, 2023), which is consistent with the findings of (Zhang et al, 2022). The spatial distribution of IE shows the trend of "decreasing from the east to the west", and regional disparities are reduced over time, which is similar to the results of the study of (Wu et al, 2023).…”
Section: The Time Evolution and Spatial Distribution Of Ie And Cesupporting
confidence: 86%
“…The digital economy has become an economy of new business models and new markets [1]. In some studies, the digital economy has been linked to various issues, such as labor [2][3][4][5][6], carbon emissions [7][8][9][10][11], population aging [12,13], artificial intelligence [14,15], foreign trade [16][17][18], and rural revitalization [19,20]. Under the continuous influence of Corona Virus Disease 2019, there are uncertainties in the global economic recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above analysis, this study develops an evaluation system for sustainable rural development from three aspects: the living conditions of rural residents, the level of agricultural production, and the level of rural environment. The study fully incorporates previous research results [42,43] and selects 27 indicators. The specific indicators are presented in Table 2.…”
Section: Sustainable Rural Developmentmentioning
confidence: 99%